Multicomponent Reaction for Selective Synthesis of Spiro[indene‐2, 7′‐isoquinoline] and 1, 2, 8, 8 a‐Tetrahydroisoquinoline Derivatives. Issue 9 (4th March 2019) - Cao, Jun; Sun, Jing; Yan, Chao‐Guo
Abstract: The piperidine promoted three‐component reaction of N ‐alkylpiperidin‐4‐ones, malononitrile and 2‐arylidene‐1, 3‐indanediones in ethanol selectively resulted in the spiro[indene‐2, 7′‐isoquinoline] and the ring‐opened cis ‐ or trans ‐1, 2, 8, 8 a ‐tetrahydroisoquinoline derivatives at room temperature or at the elevated temperature. However, the four‐component reaction N ‐alkylpiperidin‐4‐ones, malononitrile, aromatic aldehydes and 1, 3‐indanedione in refluxing ethanol mainly afforded ring‐opened cis ‐1, 2, 8, 8 a ‐tetrahydroisoquinoline derivatives in good yields and with high diastereoselectivity. A plausible domino reaction mechanism was proposed for the formation of the different polycyclic products. Abstract : The piperidine promoted three‐component reaction of N ‐alkylpiperidin‐4‐ones, malononitrile and 2‐arylidene‐1, 3‐indanediones in ethanol selectively resulted in the spiro[indene‐2, 7′‐isoquinoline] and the ring‐opened cis ‐ or trans ‐1, 2, 8, 8 a ‐tetrahydroisoquinoline derivatives at room temperature or at the elevated temperature. However, the four‐component reaction N ‐alkylpiperidin‐4‐ones, malononitrile, aromatic aldehydes and 1, 3‐indanedione in refluxing ethanol mainly afforded ring‐opened cis ‐1, 2, 8, 8 a ‐tetrahydroisoquinoline derivatives in good yields and with high diastereoselectivity.